(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Simarouba glauca belonging to the family of Simaroubaceae and is commonly known as The Paradise tree, Laxmitaru tree (Common name) or Sorgamaram (Siddha Name). It has a long history of herbal medicine in many countries. It is a native of South America and its bark decoction is given for dysentry and hence called dysentry bark. The drug contains phytochemicals such as glaucarubin, quassinoids, ailanthione, benzoquinone, holacanthone, melianone, simaroubidin, simarolide, sistosterol. Objectives: This study isto evaluate apoptotic activity of leaf extracts of Simarouba glauca against A549 Lung Cancer Cell line using MTT Assay and determining the % cell viability on increasing concentrations. Materials and Methods: Plant sample is collected and leaf Extract is prepared by adding 5gm of dried leaves powder in 50 ml aqueous extract. And to assess cell proliferation and viability MTT cell viability test was performed and apoptotic properties were identified. Aqueous extract of various concentration were used (12.5, 25, 50, 100, 200µg/ml) to confirm the increased apoptotic activity on increasing concentration. Conclusion: These findings suggested that Simarouba glauca leaf extracts inhibited lung cancer cells in a time- and dose-dependent manner. The leaf extracts of Simarouba glauca was found to be nontoxic to alveoli,pneumocytes. It can be concluded that Simarouba glauca is an important source of phytochemicals posing efficacy against lung cancer cells.